KONSEP MAQASID AL-SYARIAH SEBAGAI DASAR PENETAPAN DAN PENERAPANNYA DALAM HUKUM ISLAM MENURUT âIZZUDDIN BIN âABD AL-SALAM (W.660 H) - Harahap, Zul Anwar Ajim (TAZKIR: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
This study originated from the fact important in determining the maqasid Shariah Islamic law. Islamic law experts, among others, Al-Syatibi, Izzuddin bin Abd al-Salam explained that Islamic law is based on the maqasid sharia. Shariah religion as a whole contains a variety of well-being; either rejection of damage or taking benefit. This study focused on exploring the opinion Izzuddin ibn Abd al-Salam on the concept and its application in maqasid sharia Islamic law. The methodology used is a character study methodology, so that the analysis used is the interpretative analysis, coherence and inductive analysis. Results are that maqasid sharia is the basis for the establishment of Islamic law and its application, both in the areas of worship, muamalah and morality.